PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH BURNOUT TERHADAP KOMITMEN ORGANISASIONAL GURU - Wirajaya, I Gede Agus; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 5 No 8 (2016), 2016)
This study was conducted to determine the effect of burnot on job satisfaction and organizational commitment, the effect of job satisfactionon organizational commitment and to find job satisfaction in mediating the effect of burnout on the organizational commitment of teachers in SMAK Santo Yoseph Denpasar. The study was conducted on teacher SMAK Santo Yoseph Denpasar by the number of respondents as many as 46 teachers. The number of respondents is determined using saturation sampling technique. The data collection is done by distributing questionnaires using a 5-point Likert scale to measure 28 indicators. Data analysis technique used is path analysis . The test resultsburnout negative and significant impact on organizational commitment,burnout negative and significant impact on job satisfaction, job satisfaction positive and significant impact onorganizational commitment, as well as job satisfaction assessed the significant mediate the association between burnout to organizational commitment. The limitation of this study is the location of this research will be in the scope of the SMAK Santo Yoseph Denpasar so the results of this study can not explain the circumstances of the other school besides SMAK Santo Yoseph Denpasar.
Keywords: burnout, job satisfaction, organizational commitment.